On the Practice of Implementing Non-Formal Adult Education in the Sakha Republic (Yakutia) - Timofeeva, Raisa Egorovna (Journal of History Culture and Art Research, 2019)
The article discusses the practice of implementing non-formal education for adults at the place of residence in the national and regional conditions of the Republic of Sakha (Yakutia). Highlights strategy of education, aimed at the development of the human personality through ongoing education throughout their lives. Formal, non-formal, and informal models of education are considered, as well as the priority of non-formal adult education in modern conditions compared to formal and informal education, its features and characteristics are revealed. The conceptions of learning are substantiated, which are revealed by the methods of interviewing local residents, through conversations with them. Describes the structure, content, forms, and methods of learning, considering national mentality, authentic culture, national traditions of the locals. Point out educational and design workshops as the most justified in real life, when time dictates to man a renewal of thought and activity. Non-formal education eliminates inhibition in the minds of students, motivates them to improve the quality of life, to increase vitality. All types of activities of adult students are aimed at developing a social project that solves the problem, which is most acute for them. Their involvement in the development, and then in the practical implementation of the project, which is high-demand here and now in local conditions, is an effective mechanism that removes people's thinking from a passive state, increases their social and economic activity, enterprise, and cultural level. Aftereffect of non-formal education reflects such factors as an increase in the number of public associations in the field, growth in the number of families with moderate means, increase in the number of registered marriages, rates of birth of children, reducing the number of offenses, the number of drinkers, the emergence of strong farms, increased business activity, business enterprise of people, the desire of local residents to improve houses, courtyards, tyolbe (modern Yakut neighbor-rural community), naslegs and uluses The high motivating power of non-formal education is affirmed, which increases the general culture and gives a tangible impulse to the formation of the civil type of human behavior. It is concluded that non-formal education at the place of residence, the content of which is organically integrated into the context of real-life, activates the processes of formation of the local community, local development, and the formation of civil society.